Germans in Germany's Ethnic Neighborhoods - Anita I. Drever (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
In contrast to most research on the effects on residents of living in an ethnic neighborhood, this paper explores how living within an ethnic neighborhood affects members of the dominant ethnic group - in this case Germans - rather than the minorities that define it. The results indicate that Germans living within ethnic neighborhoods are less well off financially than their peers in other parts of the city, and are more likely to be living in large buildings in need of repair. The analysis did not however suggest that Germans living in ethnic neighborhoods have fewer social contacts, or that they are more likely to be unemployed. Indeed, Germans living within ethnic neighborhoods reported levels of satisfaction with their housing and standard of living equal to Germans elsewhere. These results would seem to paint a rosy picture of the lives of German residents of ethnic neighborhoods, were it not for a notable absence of school-aged German children within these spaces.
Keywords: 330